Polish adaptation The State Self-Forgiveeness Scale - Mróz, Justyna; Sornat, Wojciech (Kwartalnik Naukowy Fides et Ratio, 2021)
The aim of the presented study was to Polish version of The State Self-Forgiveness Scale (Wohl i in., 2008) – Skala Epizodycznego Przebaczenia Sobie. The scale is used to assess self-forgiveness after wrongdoing towards self and other persons. The scale consists of 17 items and two subscales describing feelings and actions as well as beliefs towards oneself, which are to lead to self-forgiveness. Four hundred forty four (Mage =27.8, SD=9.9) participated in the study. Both exploratory factor analysis and confirmatory analysis were performed to determine the psychometric properties (RMSEA 0,048, GFI 0,924, PCLOSE 0,556). In order to determine the internal consistency was calculated by Cronbach’s alpha (0,80-0,86). The internal validity was assessed by Heartland Forgiveness Scale. The obtained results showed that the Polish version of The State Self-forgiveness Scale as tool with good psychometric properties and to recommend it for the assessment of self-forgiveness both in research.